please.. solve.. ...
Attachments:
![](https://hi-static.z-dn.net/files/dd8/f6bde4ef7503f8565ed2241daa8d44a6.jpg)
Answers
Answered by
0
Answer:
1
Step-by-step explanation:
x=acos^3t ,y=bsin^3t
x/a=acos^3t/a=cos^3t
(x/a)^2/3=(cos^3t)^2/3=cos^2t
y/b=bsin^3t/b=sin^3t
(y/b)^2/3=(sin^3t)^2/3=sin^2t
(x/a)^2/3 +(y/b)^2/3=cos^2t +sin^2t=1
Answered by
5
Answer:
If x = a cos^3 theta and y = b sin^3 theta then prove that (x/a)^2/3 + (y/a)^2/3
Ans ) I have got the solution but the only problem is that instead of (y/a)^2/3 it's written = (y/b)^2/3
Therefore, 1 is also added ..
Check whether the given attachment is correct with ur answer
Attachments:
![](https://hi-static.z-dn.net/files/d1b/67616a8ebfd78b685fad0a940c3e1719.jpg)
Similar questions